2022
DOI: 10.1101/2022.11.24.22282651
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Comparative effectiveness of heterologous booster schedules with AZD1222, BNT162b2, or mRNA-1273 vaccines against COVID-19 during omicron predominance in the Nordic countries

Abstract: Objective: To investigate the effectiveness of heterologous booster schedules with AZD1222 (Oxford-AstraZeneca, referred to as AZD), BNT162b2 (Pfizer-BioNTech, BNT), and mRNA-1273 (Moderna, MOD) vaccines compared with primary schedules and with homologous mRNA-vaccine booster schedules during a period of omicron predominance. Design: Population-based cohort analyses. Setting: Denmark, Finland, Norway, and Sweden, 27 December 2020 to 28 February 2022. Participants: Adults that had received at least a primary va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…We give details on the propensity score generation and matching process in discussion S5. Even less common in the literature was the use of a propensity score not via matching, but with IPW instead ( 17 ). This involved weighting observations in the study sample by the inverse of their propensity for vaccination/booster (more detail is included in tables S10 and S11).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We give details on the propensity score generation and matching process in discussion S5. Even less common in the literature was the use of a propensity score not via matching, but with IPW instead ( 17 ). This involved weighting observations in the study sample by the inverse of their propensity for vaccination/booster (more detail is included in tables S10 and S11).…”
Section: Discussionmentioning
confidence: 99%
“…However, reported VEs for the first booster versus primary series vaccination in such studies have varied considerably, particularly for infection, where estimates from as high as 93% to as low as negative effectiveness can be found (16)(17)(18). Differing epidemiological and clinical landscapes, including preexisting natural immunity, evolution of COVID treatments, and contemporary variant circulation, may explain some of the differences between study results, but there still remains substantial heterogeneity in VE estimates reported by studies in the same country at around the same time, particularly in the US (19,20).…”
Section: Introductionmentioning
confidence: 99%
“…46 Even less common in the literature was the use of a propensity score not via matching, but with IPW instead. 16 This involved weighting observations in the study sample by the inverse of their propensity for vaccination/booster (more detail is included in Table 1). Compared to propensity score matching with a caliper, IPW provides potential efficiency benefits by not fully excluding any observations.…”
Section: Matching and Weightingmentioning
confidence: 99%
“…However, reported VEs for the first booster versus primary series vaccination in such studies have varied immensely, particularly for infection where estimates from as high as 93% to as low as negative effectiveness can be found. [15][16][17] Differing epidemiological circumstances, including pre-existing natural immunity and contemporary variant circulation, may explain some of the differences between study results, but there still remains substantial heterogeneity in VE estimates reported by studies in the same country at around the same time, particularly in the US. 18,19 Another factor that may explain some of the substantial differences in the results of VE studies is heterogeneity in study design and statistical methods.…”
Section: Introductionmentioning
confidence: 98%